ESTIMATION OF ORANGE MUD CRAB (Scylla olivacea) STOCKS AS THE CATCH YIELD OF FISHERMEN OF KUBU VILLAGE, KUBU RAYA DISTRICT, WEST BORNEO - Arif Triadma; INPURWANTO WI; YENI HURRIYANI (Jurnal Sains Pertanian Equator, 2019)
ABSTRACKInformation about orange mud crab (Scylla olivacea) stocks in West Kalimantan is still very minimal, especially in Kubu Village, Kubu Sub-District. The purpose of this study was to estimate the stocks of Scylla olivacea from the catch yield of fishermen of Kubu Village, Kubu Sub-District, Kubu Raya District, West Borneo Province. The method used for sampling was the Census method in which the samples to be observed were all the catches of orange mud crabs in 2 (two) collectors in Kubu Village. Sampling of S. olivacea was carried out at 1-time interval in 2 weeks for 4 (four) months. This study was conducted in September-December 2018. Based on the results of the study, S. olivacea which was caught during the study were 341 crabs, in which male crabs were caught of 255 crabs and female crabs of 86 crabs. The relationship of width and weight of male S. olivacea was negative allometric, female S. olivacea was isometric and the total male and female was isometric. The asymptotic width (L∞) of male S. olivacea was 258 mm, female was 175 mm, the total was 253.3 mm, the growth coefficient (K) of male was 0.15 per year, female was 0.21 per year, the total was 0.15 per year. The mortality of S. olivacea was mostly caused by natural mortality (M) with a value of 0.2355 per year. The rate of exploitation of S. olivacea shows that the catches carried out was still below optimal with the exploitation value (E) of 0.1673.Keyword : Stock estimation, Scylla olivacea, Width and weight relationship.